Population pharmacokinetics of teicoplanin and dosage optimization in sepsis patients based on continuous renal replacement therapy - Sun, Qian; Jian, Jiang; Zhou, Xueqiang; Hong, Zhu; Yang, Suwen; Zheng, Yanping; Wang, Siyi; Zhao, Maojun (Frontiers in Pharmacology, 2025)
PurposeIt is well known that pharmacokinetics (PK) of drugs is significantly altered in sepsis patients receiving continuous renal replacement therapy (CRRT). However, clinical studies investigating the PK of drugs administered during CRRT are limited, and appropriate dosing regimens have not yet to be definitively established. The study aimed to develop a population PK model for teicoplanin, explore significant covariates regarding to teicoplanin PK, and propose optimal dosage strategies for sepsis patients.MethodsEighty-six sepsis patients were included and plasma samples from all patients were analyzed. PK analysis was conducted on samples from 86 sepsis patients, followed by population PK analysis and simulations to ascertain the probability of target attainment (PTA).ResultsTeicoplanin was well characterized by a one-compartment PK model with first-order elimination. The presence of CRRT was associated with a lower volume of distribution (V), and gender was associated with a higher V. When MIC was set at 1 mg/L, a loading dose of 800 mg (q12h) followed by a maintenance dose of 600 mg (q24h) was necessary for male sepsis patients without CRRT, and a loading dose of 800 mg (q12h) followed by a maintenance dose of 800 mg (q24h) for male sepsis patients receiving CRRT. Female patients with sepsis required a loading dose of 1,000 mg q12h followed by a maintenance dose of 1,000 mg q24h.ConclusionTeicoplanin therapy in sepsis patients undergoing CRRT necessitates individualized dosing. A PK model-based teicoplanin dosing regimen for sepsis patients with CRRT was proposed, whereas prospective clinical study is required to validate.